(untitled) - Kornai, János (New York, 2004)
Bringing together a top flight set of contributors, this book considers the problems and prospects for creating trustworthy and reliable public institutions since the transition from socialism in Central and Eastern Europe. The focus is on "second generation" issues of democratic consolidation in states where the basic structures of the market and the state have been established. The contributors raise important issues, such as corruption and participation, largely neglected during the first stage of the transition and that are of growing importance as several countries in the region move toward entry into the European Union. Highlighting problems and prospects of democratization with comparative import to other newly democratizing areas, this volume draws on the experience of those who have lived through and studied the transition and contrasts their insights with those of generalist scholars who study government accountability and democracy.
Keywords: Communist party,Communism,Post-socialist transition